Ethical Use of Social Media Data: Beyond the Clinical Context. - Hammack, Catherine M. (Hastings Center Report, 2019)
In "Social Media, e‐Health, and Medical Ethics," in this issue of the Hastings Center Report, Mélanie Terrasse, Moti Gorin, and Dominic Sisti address and suggest recommendations for several ethical issues central to the systematic ethical analysis of the effects of social media on clinical practice, health services research, and public health. The topic is as timely as it is important: social media data collected by device and web applications are constantly increasing and might have both individual and public health benefits. The authors focus their analysis primarily on the health care context. Yet the implications of the intersection of social media data and research warrant focused consideration, as even the most thorough ethical analysis in the clinical context is not necessarily directly applicable in the research context. While many ethical issues are present in both settings, the research context poses new challenges and calls for consideration of distinct factors. In particular, because the legal framework is less protective in research, critical ethical analysis of the research‐specific issues and considerations is essential to the ethical conduct of research using social media data as well as to the design and operation of social media device and web applications themselves.